Unraveling the mechanism of hydrogen evolution on dark TiO2 obtained by pulsed laser ablation - Fakhrutdinova, Elena D.; Zinina, E. V.; Bugrova, Tatiana A.; Reutova, Olesia А.; Svetlichnyi, Valerii A.; Vodyankina, Olga V. (Kinetics and catalysis)
The influence of structural defects in TiO₂-based photocatalysts, prepared by pulsed laser ablation (Nd:YAG laser: λ 1064 nm, 180 mJ, 7 ns, 20 Hz) followed by thermal treatment in He and air, on the photocatalytic hydrogen evolution was studied. The phase composition and optical properties of the samples were determined by X-ray diffraction, Raman spectroscopy, and diffuse reflectance spectroscopy at all stages of preparation and processing. Photostimulation of dark TiOₓ samples revealed the appearance of absorption associated with the presence of oxygen vacancies (VO)/Ti³⁺ ions. A temperature-programmed oxidation (TPO) study of the sample surface in a flow of 10% O₂ in helium showed that the defects in the structure of titania were resistant to reoxidation with oxygen. According to the photocatalytic activity data in the hydrogen evolution reaction under LED irradiation at 375 nm, the high concentration of volume and surface defects in dark titanium dioxide prepared by pulsed laser ablation plays a more significant role in the process of photocatalytic hydrogen evolution than the ordered structure formed in TiO₂. The maximum efficiency was achieved due to the partial ordering of the dark TiO₂-400 structure as a result of heat treatment in air at 400°C with preservation of volume defects. Modification of the defective TiO₂-400 support with platinum by chemical and photoreduction methods showed that the defective structure of the support led to high dispersion of Pt and a ~77-fold increase in the apparent quantum yield during H₂ photoevolution regardless of the modification method. An additional increase in activity is associated with the strong metal-support interaction (SMSI) effect, which facilitates electron transfer from defects in the TiO₂-400 structure to Pt subnanoclusters.